PECULIARITIES OF THE HORMONAL COMPONENT IN SOMATO-SEXUAL PUBESCENCE WITH THE HIGH RISK OF DEVELOPMENT OF ALCOHOLISM - Лобанов, І.Ю. (World of Medicine and Biology, 2016)
It was carried the pilot study in Poltava among 68 adolescents and young adults 16-19 years old in order to study the prognostic impact of cerebro-organic and hormonal status on the risk of developing alcohol dependence.It was determined in their blood levels of testosterone, progesterone, estradiol, cortisol and adolescents are defined morph types (87.7 %). The changes were examined hormonal profile compared to standard values, due to violations of the hormonal regulation of homeostasis level as a result of «malignant perinatal track».Monitor hormonal teenagers in order to identify high-risk groups is necessary for the prevention of alcohol dependence and alcohol abuse youth.
Keywords: аlcohol addiction; malignant perinatal follows puberty; hormones